Philosophy as a religious experience in Plato - Newman, Deron Scott (The University of Edinburgh, 2000)
Plato is a philosophical theologian in whom philosophy and theology are synonymous, and the way of philosophy a religious endeavour. However, contemporary scholarship overlooks the importance of the religious dimension of Plato's philosophy, and in particular, neglects an examination of the theological ideas that are involved in this understanding. In answer to this, the thesis argues that, in Plato, philosophy is a religious human experience, that it is within such a perspective that Plato's philosophical theology can be properly understood, and that such a perspective provides both theological and philosophical insights. The thesis offers a unique contribution to scholarship in that it examines the issues of Plato's philosophical theology from the perspective of Plato's philosophy as a religious experience. Secondly, it relates the question of the religious nature of Plato's philosophy to the issue of humanity by seeing Plato's philosophy as a means of human transformation and as a religious way of life and existence. And thirdly, by interacting with recent scholarly interpretation and commentary, seeks ways in which such a perspective provides insights for contemporary theological and philosophical thought. To examine these issues, the thesis employs two overarching themes: philosophy as a religious experience as involved directly with the question of the human situation and life, and the human experience of the divine in Plato. Chapters One and Two consider, respectively, Plato's philosophy as a way of salvation and transformation in the individual and society, and the idea of the philosophical life. Chapters Three through Five examine the religious experience of the Forms as divine reality and the meaning to human existence, the idea of the personal relationship between the philosopher and the divine, and the philosophical experience of divine inexpressibility. Lastly, in the Conclusion, I seek to apply the idea of Plato's philosophy as a religious experience to a contemporary context by raising several ofthe important issues that are involved when Plato's philosophy is realised as a religious way of life today. The thesis concludes that what is manifested in Plato is a deep interrelation between philosophical and religious thought which gives rise to a vibrant and insightful philosophical theology of Plato's philosophy as a religious human experience.